The The Implementation Of Game Method To Increase Student’s Math Learning Activities In Smp Negeri - Nisda Putri (Jurnal Ilmiah Pendidikan Scholastic, 2017)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do", which describe something in their own way, showing for example, tried to practice skills and tasks that require What Knowledge they have earned. The problems to be examined in this study are: a How improve mathematics learning outcomes by using the game in class IX SMP Negeri 2 P Ainan academic year 2014-2015? b. The steps made in improving learning outcomes math class IX students? The results showed that study using the game in class IX SMPN 2 Painan, on learning of Mathematics, encourage student learning activities to teach well so spur students to obtain satisfactory academic achievement. Of the 10 observed activities, 7 of them are classified into medium category and 3 of them fall into the less category. The three activities gradually increase in each cycle, the three activities are preparing places, materials and tools by 25.93%, expressing the idea of ​​11.11% and reading the rules of the game and books of 29.63% and each Has increased, become Preparing places, materials and tools of 55.56%, revealed the idea of ​​66.67% and for the activity of reading the rules of the game and books increased by 74.04%. Achievement learn student mathematics obtained grade average value in cycle I equal to 69,62 increase become 73,51 in cycle II. The percentage of students who reached the completeness standard also increased in the first cycle of 88.88% (Category Good), increased to 100% (Category Special Category) in cycle II. Thus the game method can improve the activity and achievement of learning mathematics students SMPN 2 Painan Lesson Year 2014/2015. Student journals are known by the use of game methods to make learning more fun, learning less tense but still concentrating. Students more quickly understand the concept of geometry and measurement by appreciating the role played.